[PP.30.05] BLOOD PRESSURE IN RELATION TO 24-HOUR URINARY SODIUM EXCRETION AND RENAL SODIUM HANDLING. (September 2016) - Stolarz-Skrzypek, K.; Bednarski, A.; Franczyk, A.; Folta, M.; Barton, H.; Olszanecka, A.; Kloch-Badelek, M.; Kielbasa, G.; Kawecka-Jaszcz, K.; Czarnecka, D.
Abstract : Objective: There is abundant evidence that sodium intake is related to blood pressure (BP). However, the relationship varies between individuals and is probably determined by renal sodium handling. We investigated ambulatory BP in relation to interactions between sodium dietary intake and renal handling, as assessed by 24-hour urinary sodium excretion (24hUVNa) and endogenous lithium clearance, respectively. Design and method: We recruited from general population 192 individuals, never treated with antihypertensive medications. We administered standardized questionnaires to obtain information on subjects' medical history and life style. SpaceLab 90207 monitors were programmed to measure blood pressure each 15 min during daytime (6:00–22:00) and each 30 min night-time. Blood and 24-hour urine samples were collected. We measured urine and plasma lithium and calculated fractional excretion of lithium (FELi) as the marker of proximal sodium handling. A higher FELi indicates that less sodium and water is reabsorbed in the proximal tubule. Results: The study group included 87 men and 105 women, mean age 40.5 years, office BP 124.7/84.3 mmHg, 24hUVNa 171 mmol/24 h. In adjusted analyses, FELi was negatively related to night-time systolic BP (r = -0.0095, P = 0.035) and 24hUVNa showed tendency towards a positive relation to night-time systolic BP (r = 0.022, P = 0.06). However, a significant association between 24hUVNa and night-time BP was present only in the subgroup with upper than median FELi (> = 17.3%). We observed a tendency (P = 0.09) towards more steeper slope of the regression line of systolic night-time BP over 24hUVNa in individuals with upper then median FELi as compared to subjects with lower than median FELi. Moreover, day-night systolic BP difference decreased with decreasing FELi (r = 0.067, P = 0.024). Conclusions: In our high-salt intake population sample, sodium dietary intake and proximal tubular sodium handling both showed association with night-time systolic BP. This relation was observed only in individuals with lower proximal sodium reabsorption, that might suggest the importance of extrarenal mechanisms of sodium homeostasis in BP regulation. Moreover, higher proximal sodium reabsorption, as measured by lower fractional lithium excretion, is related to lower day-night systolic BP difference, and might be postulated as one of the mechanisms responsible for blunted diurnal BP profile.